Species substrate specificity of growth of lactobacilli isolated from vaginal biotope on culture medium with inclusions of different types of natural nanopolysaccharides - N. M. Shabanova (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The article presents the research of substrate and prebiotic properties of natural nanopolysaccharides for several species of lactobacilli isolated from vaginal biotope of women, with assessment of their species combinations. Most of typeable lactobacilli species prefer to grow on media containing polysaccharides, mainly in nutrient broth supplemented with galactomannan and carageenan. Using galactomannan increases the frequency of detection, as compared with the isolation from the starting material, twice.